Odpowiedzi

Najlepsza Odpowiedź!
2010-03-25T13:52:22+01:00
A) 3:4=x:2
3*2 = 4x
6 = 4x /:4
x = 1,5

b)3 przez 2 = m przez 1,6
3*1,6 = 2m
2m = 4,8 /:2
m = 2,4

c 0,8 :7 = 0,32 : x
0,8m = 0,32*7
0,8m = 2,24
m = 2,8

Rozwiąż równania
a) 3,5 przez 2,8 = x przez 3,2
3,5*3,2 = 2,8x
11,2 = 2,8x
x = 4

b) 4-x przez 6 = 5-2x przez 7
6(5-2x) = 7(4-x)
30-12x = 28-7x /+12x -28
5x = 2 /:5
x = 2/5


c) -5x+2 przez 4 = 2x +1 przez 2
4(2x+1) = 2(-5x+2)
8x+4 = -10x+4 /+10x -4
18x = 0
x = 0

proszę bardzo :)
3 5 3
2010-03-25T13:58:10+01:00
1
a) 3:4 = x:2
x=3*2 : 4 = 6:4 = 1,5

b) 3:2 = m:1,6
m=3*1,6 : 2 = 4,8:2 = 2,4

c) 0,8:7 = 0,32:x
x=7*0,32 : 0,8 = 2,24:0,8 = 2,8

2
a) 3,5:8 = x:3,2
x=3,5*3,2 : 0,8 = 11,2 : 0,8 = 14